2001
DOI: 10.1097/00008571-200111000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Functional evaluation of cytochrome P450 2D6 with Gly42Arg substitution expressed in Saccharomyces cerevisiae

Abstract: A single amino acid-substituted mutant protein, CYP2D6 (G42R) was expressed in Saccharomyces cerevisiae and its enzymatic properties were compared with those of other single (P34S, R296C and S486T) and double amino acid-substituted mutant proteins (P34S/S486T and R296C/S486T) expressed in yeast cells, all of which were known to occur in the CYP2D6 gene as single nucleotide polymorphisms. The protein levels of G42R, P34S and P34S/S486T in microsomal fractions and their oxidation capacities towards debrisoquine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 32 publications
4
26
0
Order By: Relevance
“…Previous findings indicated that substitution located in the N-terminal region-such as G42R 49,50 and P34S…”
Section: 25mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous findings indicated that substitution located in the N-terminal region-such as G42R 49,50 and P34S…”
Section: 25mentioning
confidence: 99%
“…50 Similarly, lower enzyme activity was observed in G42E substitution with lower microsomal contents and higher K m value for oxidation of debrisoquine than the wild type, due to lower efficiency of the protein in its anchoring to endoplasmic reticulum membranes. 53 Therefore, CYP2D6*71 could be a putative PM allele.…”
mentioning
confidence: 95%
“…7) Briefly, the mutation-bearing plasmid was digested with HindIII, and the resultant fragment was inserted into HindIII-digested dephosphorylated pGYRI and transformed into Escherichia coli (E. coli) HB101. The yeast expression vector pGYRI has a glyceraldehyde 3-phosphate dehydrogenase (GAPDH) promoter and includes the yeast NADPH-CYP reductase gene.…”
Section: Computer-assisted Molecular Modeling ---mentioning
confidence: 99%
“…[4][5][6] In our previous project, CYP2D2 (P450BTL) was purified employing bunitrolol (BTL) 4-hydroxylase as the index of CYP2D2 functions. 4) BTL is a β-adrenoceptor blocking agent, and rat CYP2D2, 4) as well as human CYP2D6, 7) catalyzes BTL 4-hydroxylation with relatively low Km values. Our interest has also been directed to the mechanism(s) responsible for the stereoselectivity in the oxidation of various chiral substrates by CYP2D enzymes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation